Reptiles - Drew, David; Ruth, Trevor; Longman (Harlow, England Longman, 1997)
An introduction to reptiles, covering various species, their habitats, behaviours, and characteristics, accompanied by detailed illustrations.
For children aged 7-10 years
Keywords: Reptiles, Reptiles$1 (BJuvenile literatures